Gut bacteria: an etiological agent in human pathological conditions - Islam, Md Minarul; Mahbub, Nasir Uddin; Hong, Seong-Tshool; Chung, Hea-Jong (Frontiers in Cellular and Infection Microbiology, 2024)
Through complex interactions with the host’s immune and physiological systems, gut bacteria play a critical role as etiological agents in a variety of human diseases, having an impact that extends beyond their mere presence and affects the onset, progression, and severity of the disease. Gaining a comprehensive understanding of these microbial interactions is crucial to improving our understanding of disease pathogenesis and creating tailored treatment methods. Correcting microbial imbalances may open new avenues for disease prevention and treatment approaches, according to preliminary data. The gut microbiota exerts an integral part in the pathogenesis of numerous health conditions, including metabolic, neurological, renal, cardiovascular, and gastrointestinal problems as well as COVID-19, according to recent studies. The crucial significance of the microbiome in disease pathogenesis is highlighted by this role, which is comparable to that of hereditary variables. This review investigates the etiological contributions of the gut microbiome to human diseases, its interactions with the host, and the development of prospective therapeutic approaches. To fully harness the benefits of gut microbiome dynamics for improving human health, future research should address existing methodological challenges and deepen our knowledge of microbial interactions.